2020
DOI: 10.1007/s13143-020-00211-4
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Structure for Convective Development in the Events of Cloud Clusters over the Korean Peninsula

Abstract: This study examines atmospheric structures causing convective development in the events of cloud cluster (CC) over the Korean peninsula using the analysis and forecast data of National Centers for Environmental Prediction (NCEP) climate forecast system reanalysis (CFSR) and observation data. Two CC types-CCs associated with meso-α-scale lows (CCMLs) and mesoscale troughs (CCMTs)-were investigated. The common atmospheric structure for convective development in CC events is comprised of i) a strong southwesterly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Similarly, TGM concentrations were higher in the early in the morning and midnight times reported by Schmolke et al [36]. Such night-time maximums of TGM concentration [33,36,43,44] have been due to mercury releases in the night-time inversion layer from surface accumulations. The potential sources of TGM in the investigation ground are from coal-based power plants, vehicular discharge, and squander burning [11,12,43].…”
Section: Temporal Variability Of Atmospheric Mercury In Chennai Coastmentioning
confidence: 59%
See 1 more Smart Citation
“…Similarly, TGM concentrations were higher in the early in the morning and midnight times reported by Schmolke et al [36]. Such night-time maximums of TGM concentration [33,36,43,44] have been due to mercury releases in the night-time inversion layer from surface accumulations. The potential sources of TGM in the investigation ground are from coal-based power plants, vehicular discharge, and squander burning [11,12,43].…”
Section: Temporal Variability Of Atmospheric Mercury In Chennai Coastmentioning
confidence: 59%
“…Such night-time maximums of TGM concentration [33,36,43,44] have been due to mercury releases in the night-time inversion layer from surface accumulations. The potential sources of TGM in the investigation ground are from coal-based power plants, vehicular discharge, and squander burning [11,12,43]. The short-term measurements of TGM in china report recommend that the TGM ranges from 2.5 to 3.5 ng/m 3 for east beach front territories of China, 1.94 to 3.22 ng m −3 for Indochina peninsular regions [29].…”
Section: Temporal Variability Of Atmospheric Mercury In Chennai Coastmentioning
confidence: 99%
“…Furthermore, the nocturnal enhancement of low-level jets over southeastern China contributed to increased moisture transport, a low-level ascent, and elevated convective instability (Chen et al, 2017;Zhang et al, 2022). Additionally, Lee et al (2021) examined how upward motion in a convergence zone over the Yellow Sea enhances convection in air parcels in an elevated layer of convective instability.…”
Section: Mesoscale Process During the Development Of Cold-type Cloudsmentioning
confidence: 99%
“…Climatologically, different characteristics also exist between heavy rainfall episodes in August and in the Changma period. First, heavy rainfall caused by the Changma front tends to occur regularly every year, whereas the August heavy rainfall episodes caused by a quasi-stationary front do not occur regularly because synoptic systems such as typhoons can substantially influence them (e.g., Kim et al, 2006;Byun and Lee, 2012;Cheung et al, 2018;Lee et al, 2021). Suzuki, (1967) reported that the amount of August rainfall in Japan was composed mainly of rainfall caused by thunderstorms and typhoons.…”
Section: Introductionmentioning
confidence: 99%